PENGARUH PENDEKATAN HUMANISTIK GURU SEJARAH KEBUDAYAAN ISLAM TERHADAP AKHLAK PESERTA DIDIK DI MTSN 3 ENREKANG - Zahrina, Nurul; Bunyamin, Andi; Syahrul, Muhammad; Mustamin; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the humanistic approach of Islamic Cultural History (SKI) teachers which includes empathy, unconditional positive regard, and sincerity on the morals of eighth-grade students at MTsN 3 Enrekang. This study uses a quantitative approach with an ex post facto research type. The study population was 122 eighth-grade students, while the sample was 55 students determined using a simple random sampling technique with the Slovin formula. The data collection technique used a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was carried out through descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination with the help of the SPSS program. The results of the study indicate that simultaneously the humanistic approach of SKI teachers has a positive and significant effect on the morals of students, evidenced by the calculated F value of 17.819 and a significance value <0.001. Partially, the empathy variable has a significant effect with a calculated t value of 2.648 and Sig. 0.011, unconditional appreciation has a significant effect with a t-value of 4.341 and Sig. <0.001, and sincerity has a significant effect with a t-value of 2.795 and Sig. 0.007. The R Square value of 0.512 indicates that the three variables are able to explain 51.2% of the variation in students' morals, while 48.8% is influenced by other factors outside the study. The variable that provides the largest contribution is unconditional appreciation with an effective contribution of 25.30%, followed by sincerity of 15.33%, and empathy of 10.56%. Thus, the humanistic approach of SKI teachers has a positive and significant effect on the formation of morals of class VIII students at MTsN 3 Enrekang.